2011
DOI: 10.1002/jhm.804
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and management of hypertension in the inpatient setting: A systematic review

Abstract: BACKGROUND: Hypertension (HTN) is a major cardiovascular risk factor yet control rates remain suboptimal. Thus, improving recognition, treatment, and control of HTN by focusing on novel populations such as hospitalized patients is warranted. Current consensus guidelines do not address inpatient HTN, and little is known about HTN prevalence or patterns of care in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 24 publications
1
42
0
Order By: Relevance
“…Further evidence for a high prevalence of HTN among hospitalized patients comes from a report that over 35 % of males and 39 % of females have HTN listed as a secondary diagnosis at the time of hospital discharge [7]. Finally, a systematic review of reports describing inpatient HTN prevalence based on BP measurements found estimates ranging from 50.5 to 72 % [8].…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Further evidence for a high prevalence of HTN among hospitalized patients comes from a report that over 35 % of males and 39 % of females have HTN listed as a secondary diagnosis at the time of hospital discharge [7]. Finally, a systematic review of reports describing inpatient HTN prevalence based on BP measurements found estimates ranging from 50.5 to 72 % [8].…”
Section: Introductionmentioning
confidence: 97%
“…Some evidence suggests that nonemergent HTN is overdiagnosed and overtreated in the inpatient setting [20,21]. Additional reports suggest opportunities to improve follow-up care for hypertensive patients after hospital discharge [8]. This review focuses on the diagnosis and management of nonemergent elevated BP observed in the inpatient setting.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…These figures are consistent with the high percentage (>50%) reported in the past 15 years. A review of the peer-reviewed literature on hypertension since 1976 using a predetermined search algorithm revealed that between 56.4% and 72.6% of inpatients had hypertension [3]. Two crosssectional studies in 2006 and 2009 from single-university centers in the U.S. and Italy reported hypertension prevalence of 72.6% among hospitalized patients [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…Many patients who have persistently elevated BP in the hospital setting will continue to have high BP following hospital discharge [3]. Therefore; it may be worthwhile to identify these patients and to control their BP while they are hospitalized at internal medicine departments.…”
Section: Introductionmentioning
confidence: 99%